Implementation of the Agency Level Financial Application System (SAKTI) for Financial Management at the Regional Office of the Ministry of Religion of West Sulawesi Province. - Suryanti, Suryanti; Hasniaty, Hasniaty; Wahyu, Wahyu (YUME : Journal of Management, 2024)
This study aims to evaluate the effectiveness and challenges in implementing the Agency-Level Financial Application System (SAKTI) at the Regional Office of the Ministry of Religious Affairs of West Sulawesi Province. A qualitative approach was used in this study, where data were collected through in-depth interviews with a number of key informants who were directly involved in financial management at the agency. The results of the study indicate that SAKTI is generally considered very effective in improving the efficiency, accuracy, and transparency of financial management. However, several challenges are still faced, such as internet network problems, unstable server performance, and the frequency of system maintenance that often disrupts user activities. Management provides strong support for the implementation of SAKTI, but more routine evaluation and monitoring are recommended to ensure system optimization. Based on these findings, this study recommends improving technology infrastructure and developing additional features in the application to support users in more efficient financial management. Keywords: SAKTI, financial management, challenges, effectiveness